Apurinic endonucleases from Saccharomyces cerevisiae. - Armel, P R (1978)
Three endonuclease activities have been partially purified from Saccharomyces cerevisiae on the basis of their activity against x-irradiated closed-circular supercoiled bacteriophage PM2 DNA. These endonucleases also nick apurinic DNA and two out of the three activities incise DNA UV-irradiated with high doses. The endonuclease activities have also been distinguished on the basis of their magnesium requirement and sensitivity to EDTA.